Oil palm inflorescence (Elaeis guineensis Jacq.) ash and pirimiphos-methyl dust application for control of Oryzaephilus surinamensis infestation on stored date palm fruit (Phoenix dactylifera) (2013)
The efficacies of male oil palm inflorescence ash (OPIA) and pirimiphos-methyl dust (PMD) were assessed for possible control of Oryzaephilus surinamensis infestation of the date palm fruit Phoenix dactylifera. Male OPIA at concentrations of 0.625 g/25 g of fruit and 1.25 g/25 g as well as PMD at the prescribed dosage of 0.0125 g/25 g were tested on pristine and simulated dates using four replicates per treatment for exposure periods of 5 and 10 weeks. Efficacy was measured on the rate of mortality and emergence of O. surinamensis at various development stages. Results showed increased larval and adult mortality on both pristine and simulated dates and decreased larval and adult emergence of the pest exposed to 1.25 g of OPIA. Five days exposure to PMD recorded a significantly high mean mortality of adult O. surinamensis and no emergence. The authors concluded that exposure to OPIA at the concentration of 1.25 g/25 g for five weeks could be used in possible control of O. surinamensis infestation of palm date fruit with mechanical damages during storage.